Penerapan Media Konkret Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Siswa Kelas 1 SDN Baluase - kasmawati; putriwanti; Dyah Aini Purbarani (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2024)
This research aims to improve the mathematics learning outcomes of class I students at SDN Baluase through the application of concrete media. Concrete media was chosen because of its ability to help students understand abstract mathematical concepts through the manipulation of real objects. This research uses a classroom action approach (PTK) which is carried out in two cycles, with each cycle consisting of planning, implementation, observation and reflection. Data was collected through test sheets, observations and documentation, which were then analyzed descriptively to measure improvements in student learning outcomes. The subjects of this research were 30 class I students. Data collection was carried out through quantitative data from student test results, while qualitative data was obtained from student test sheets and observation sheets during the learning process. The research success indicator is set with a completion target of 75%. The research results show that the application of concrete media in mathematics learning significantly improves student learning outcomes. In the pre-cycle, only 40% of students achieved completeness with a KKM score of 75. After implementing concrete media, there was a significant increase to 66% in Cycle I and 97% in Cycle II. This research shows that the use of concrete media in mathematics learning in class I at SDN Baluase significantly improves student learning outcomes. The results obtained show a consistent increase in students' understanding of mathematical concepts, object manipulation abilities, and self-confidence. This increase shows that concrete media is effective in helping students understand mathematical concepts better, so that the learning process becomes more interactive and interesting. With concrete media, students are more easily involved in learning and improve learning outcomes and understanding and mathematical skills.